Navigating International Investment Law in Southeast Asia: The Case of Unfair Competition in Indonesia’s Mining Sector - Agus Lanini; Elisabeth Christina Tan; Sergi Fernandez Alejandro (International Law Discourse in Southeast Asia, 2026)
This paper explores the intersection between international investment law and domestic regulatory frameworks in Southeast Asia, with a particular focus on unfair competition in Indonesia’s mining sector. As Southeast Asia continues to attract foreign direct investment (FDI), legal disputes involving foreign investors and host states have become more frequent, particularly in resource-rich industries. Using Indonesia as a case study, this research analyzes how allegations of unfair competition—such as discriminatory licensing, state favoritism toward domestic enterprises, and lack of transparency—can trigger claims under international investment agreements (IIAs). The novelty of this paper lies in its focus on the underexplored tension between international investment protections and national efforts to regulate competition in strategic sectors. Through doctrinal legal analysis and selected case reviews, the paper highlights inconsistencies between Indonesia’s domestic legal framework and its international obligations, particularly under bilateral investment treaties (BITs). The contribution of this study is twofold: first, it provides a critical legal mapping of how unfair competition claims in the mining sector may escalate to investor-state dispute settlement (ISDS); second, it offers policy recommendations to harmonize investment protection with fair competition principles. Ultimately, this paper argues that unless Southeast Asian countries, particularly Indonesia, reform their investment governance and competition policies, they risk increased litigation and a chilling effect on sustainable investment. This research adds to the growing discourse on how developing countries can balance investor protection with national economic sovereignty.